2019
DOI: 10.3390/ijms20194830
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin Mitigates Immune-Induced Epithelial Barrier Dysfunction by Campylobacter jejuni

Abstract: Campylobacter jejuni (C. jejuni) is the most common cause of foodborne gastroenteritis worldwide. The bacteria induce diarrhea and inflammation by invading the intestinal epithelium. Curcumin is a natural polyphenol from turmeric rhizome of Curcuma longa, a medical plant, and is commonly used in curry powder. The aim of this study was the investigation of the protective effects of curcumin against immune-induced epithelial barrier dysfunction in C. jejuni infection. The indirect C. jejuni-induced barrier defec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
51
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 52 publications
3
51
1
Order By: Relevance
“…Since then, abiotic IL-10 −/− mouse model has been successfully employed in many studies [48][49][50][51]. In recent studies, the abiotic IL-10 −/− mouse model was also used to determine the barrier protective and anti-inflammatory effects on C. jejuni infection using curcumin or vitamin D [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…Since then, abiotic IL-10 −/− mouse model has been successfully employed in many studies [48][49][50][51]. In recent studies, the abiotic IL-10 −/− mouse model was also used to determine the barrier protective and anti-inflammatory effects on C. jejuni infection using curcumin or vitamin D [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the increased concentrations of pro-inflammatory cytokines such as TNF-α, IL.-1β and IL-6 in C. jejuni infected co-cultures were down-regulated after curcumin treatment [99]. These results indicate that curcumin in competition to TLR-4 binding antagonized local and systemic inflammatory responses triggered by bacterial LPS/LOS [99,100]. Moreover, it has been reported that the competition between curcumin and LPS/LOS to bind TLR-4 inhibited the MyD88-dependent pathway [101].…”
Section: Activation Of Tlr-4 Signaling By C Jejuni Lipooligosaccharimentioning
confidence: 95%
“…Interestingly, there are several natural plant products such as curcumin derived from Curcuma longa acting as highly effective TLR-4 antagonists by non-activate binding leading to competitive inhibition of LPS/LOS functions [98]. Recently, it has been demonstrated that apoptosis induction, tight junction redistribution, and increased inflammatory responses upon C. jejuni infection were down-regulated after curcumin treatment in a co-culture model of human colon epithelial cells HT-29/B6-GR/MR and immune THP-1 cells [99]. Additionally, curcumin could effectively ameliorate the campylobacteriosis symptoms including apoptosis, T-cell mediated inflammatory responses and colonic barrier dysfunction, observed in C. jejuni infected IL10 −/− mice [99].…”
Section: Activation Of Tlr-4 Signaling By C Jejuni Lipooligosaccharimentioning
confidence: 99%
See 2 more Smart Citations